Click here to load reader

Section 6.1 - 6.2 Notes Laplace Transforms · Section 6.1 - 6.2 Notes Laplace Transforms Name: ... between the Laplace

  • View

  • Download

Embed Size (px)

Text of Section 6.1 - 6.2 Notes Laplace Transforms...

  • MATH 207003 Differential Equations Dr. Lori Alvin

    Section 6.1 - 6.2 Notes Laplace Transforms


    A short table of Laplace transforms appears on the last page. We begin by reviewing somebasic calculus results before introducing the Laplace Transform.

    Review: Limits of exponential functions

    We consider exponential functions of the form f(t) = eat, where a is a number. The generalbehavior of eat as t is determined by whether a is positive, negative, or zero.



    y=e-2 t






    y=e0 t =1

    In general, limt

    eat =

    0, a < 0;1, a = 0;, a > 0.

    Review: Improper integrals

    In Calculus 3 we studied improper integrals; integrals of the form a

    f(x) dx

    The symbolaf(x) dx is an abbreviation of the expression



    f(t) dt

    If the limit exists, we say the improper integralaf(x) dx converges, otherwise we say the

    improper integralaf(x) dx diverges.

  • Exercise 1. Decide whether the following improper integrals converge or diverge. For thosethat converge, compute their values.(a)

    0e4x dx

    (b)0te3t dt

    (c)0et/2 dt


    1x lnx


    Exercise 2. For which values of s does the integral0est dt converge?

    The Laplace Transform

    The Laplace Transform is another way of writing a function.Usually when we talk about a function, we talk about its values. We evaluate the function

    by substituting numbers into the formula. For example, we evaluate f(x) =1

    4 + x2at x = 3

    by substituting 3 into the formula: f(3) =1

    4 + 32=


    13. Two functions f(x) and g(x) are

    the same if every possible evaluation produces the same result, that is if f(a) and g(a) arethe same for every a in the domains of f and g.There are other ways to test functions, that is, to make them produce numbers. Oneway is to multiply them with other functions and then integrate. We can think of this as ageneralization of evaluation.Given functions f and g defined on the interval [0,), we can integrate f against g, thatis, compute


    f(t)g(t) dt

    For many choices of g, the result will be a number. We will mainly be interested in theresults of integrating f against exponential functions, such as e4t:


    f(t)e4t dt

    or, more generally, 0

    f(t)est dt.

    For different values of s, the result will be a number, depending on s.

    Definition The Laplace transform function Y of the function y is defined by

    Y (s) =


    y(t)est dt

    for all numbers s for which the integral converges.

    Page 2

  • Example. Compute the Laplace transform of y(t) = e5t and state its domain.

    We can think of the value of Y (s) as measuring how closely the function y(t) resembles thefunction est: when Y (s) is very large, the function y(t) closely resembles est, and when Y (s)is small, the function y(t) is very different from est.

    Page 3

  • Notation.

    If y(t) is a function, we may write L [y(t))] for its laplace transform. So

    L [e5t] =1

    s 5for s > 5

    The Laplace Transform and Derivatives

    The reason for even considering the Laplace transform is because of the nice relationshipbetween the Laplace transform of a function y(t) and the Laplace transform of its derivativedydt


    Laplace Transform of Derivatives Given a function y(t) with Laplace transform L [y],

    the Laplace transform ofdy



    ]= sL [y] y(0).

    This is a consequence of the definition of the Laplace transform and integration by parts:





    )est dt.

    Page 4

  • Exercise 3. Verify that the formula L[dydt

    ]= sL [y] y(0) holds for the function y(t) = t.

    That is, compute L [t], compute L [1], and show that L [1] = sL [t] 0.


    The following standard properties of integration

    f(t)+g(t) dt =

    f(t) dt+

    g(t) dt and

    cf(t) dt = c

    f(t) dt lead to the corresponding properties for the Laplace transform:

    L [f + g] = L [f ] + L [g]

    [cf ] = c[f ].

    Page 5

  • General Procedure for Solving a First-order Linear equation using Laplace trans-forms

    Given an initial value problem


    dt= a(t)y + b(t), y(0) = y0

    (Usually a(t) is a constant.)

    1. Compute the Laplace transform of both sides, using the identity L[dydt

    ]= sL [y] y(0)

    on the left-hand side.

    2. Solve for L [y]: you will have a solution of the form L [y] = g(s).

    3. Break g(s) down as a sum of simple functions (hopefully the ones that appear in the tableof Laplace transforms on page 626). Use partial fractions if necessary.

    4. Compute the inverse Laplace transform of g(s): your answer will be

    y(t) = L 1[g(s)]

    Example. Solve


    dt= y t y(0) = 1

    using Laplace transforms.

    Page 6

  • Discontinuous functions in differential equations

    The Heaviside function

    ua(t) =

    {0, if t < a;1, if t a.

    The Laplace transform of ua(t):

    L [ua] =eas


    The Heaviside function is useful in modeling physical situations where something changesabruptly at a certain time.

    Example. Solve the initial value problem


    dt= y + 4u2(t); y(0) = 3

    Page 7

  • .

    Page 8

  • .

    Remarks. The answer produced by Solution (B) is actually the same as the answer producedby Solution (A). You can check that they are the same by simplifying the answer from (B):

    4u2(t)(1 e(t2)) + 3et =

    3et, if t < 2;

    4(1 e(t2)) + 3et, if t 2.

    and the second part simplifies as (3 4e2)et + 4.

    Page 9

  • Example. Solve the initial-value problemdy

    dt= 2y+e3t, y(0) = 1 using Laplace transforms.

    Page 10

  • Some Laplace Transforms and RulesSee the table on p. 626 of the text for the full list.

    Original Function y(t) = L 1[Y (s)] Laplace Transform Y (s) = L [y(t)]

    y(t) = 1 Y (s) =1


    y(t) = eat Y (s) =1

    s a(s > a)

    y(t) = t Y (s) =1


    y(t) = tn Y (s) =n!


    y(t) = ua(t) Y (s) =eas

    s(s > 0)

    Rule for Laplace Transform Rule for Inverse Laplace Transform


    ]= sL [y] y(0) = sY (s) y(0)

    L [y + w] = L [y] + L [w] L 1[Y +W ] = L 1[Y ] + L 1[W ] = y(t) + w(t)

    L [y] = L [y] = Y (s) L 1[Y ] = L 1[Y ] = y(t)

    L [ua(t)y(t a)] = easL [y] = easY (s) L 1[easY ] = ua(t)y(t a)

    L [eaty(t)] = Y (s a) L 1[Y (s a)] = eatL 1[Y ] = eaty(t).

    Page 11